Evaluation of the effect of rectus sheath block and transversus abdominis plan block on sevoflurane and fentanyl consumption in laparoscopic cholecystectomy: A randomized controlled study - Keleş, Ecem; Gültekin, Ahmet; Yildirim, Ilker; Arar, Cavidan; Topçu, Birol (The European Research Journal, 2025)
Objectives: We aimed to compare the total amount of inhalation anesthesia consumed and the amount of fentanyl used as an additional dose in cases where transversus abdominis plane and rectus sheath blocks were applied for postoperative analgesia. Methods: Eighty patients aged 18-75 years, classified as ASA I-II, who were scheduled for laparoscopic cholecystectomy, were included. The patients were divided into two groups: those who received a combination of transversus abdominis and rectus sheath blocks under general anesthesia (Group B, n=40), and those who received analgesia with tramadol under general anesthesia (Group C, n=40). Throughout the procedure, both groups were monitored to maintain the entropy target value between 40-60 with a maximum MAC value of 1.3. At the end of the procedure, the total amount of inhalation agent consumed, and the additional need for superficial anesthesia/analgesia, as well as the total amount of fentanyl added as an extra dose, were recorded. Results: Comparing the total amount of inhalation agent consumed throughout the case, it was found to be 27.05±7.43 mL in Group C (Control group) and 12.25±4.34 mL in Group B (Block group), with a statistically significant difference between the groups. There was a significant difference in the need for additional intraoperative and the total amount of fentanyl consumed between the groups (P<0.05). Conclusions: In laparoscopic cholecystectomy cases, we observed that the use of transversus abdominis plane block and rectus sheath block combined with standardized general anesthesia monitored by entropy reduced the amount of inhalation agent consumed, as well as the need for additional intraoperative and total opioid consumption.